Cover Picture: NMR Hyperpolarization Techniques of Gases (Chem. Eur. J. 4/2017). Issue 4 (5th December 2016) - Barskiy, Danila A.; Coffey, Aaron M.; Nikolaou, Panayiotis; Mikhaylov, Dmitry M.; Goodson, Boyd M.; Branca, Rosa T.; Lu, George J.; Shapiro, Mikhail G.; Telkki, Ville‐Veikko; Zhivonitko, Vladimir V.; Koptyug, Igor V.; Salnikov, Oleg G.; et al.
Abstract : Nuclear spin polarization can be significantly increased through the process of hyperpolarization, leading to an increase in the sensitivity of nuclear magnetic resonance experiments by 4–8 orders of magnitude. Hyperpolarized gases can be more readily separated from the compounds used to mediate the hyperpolarization processes. These pure hyperpolarized gases enabled many novel MRI applications including the visualization of void spaces, imaging of lung function, remote detection, etc. This article covers the fundamentals of the preparation of hyperpolarized gases and focuses on selected applications of interest to biomedicine and materials science. More information can be found in the Minireview by E. Y. Chekmenev et al. onpage 725 ff.